Fragmentary transmissions: on the poetics, practice, and futurism of Listener. Issue 2 (4th May 2019) - Kite, Suzanne; Baudemann, Kristina
Abstract : Listener is a foray into the Indigenous future. In her performance Kite impersonates a cloaked diasporic Oglála wanderer who listens for transmissions beyond the range of the humanly audible. This article provides different frameworks with which to approach Listener . Kite (Oglála Lakȟóta) will give insight into her background, introduce her art, and discuss some of the guiding questions behind it. This is followed by a dialogue with Baudemann, a non-Indigenous scholar who is interested in Kite's motivations to create Listener, her use of technology, and her view of the future. This second part is a transcription of an interview conducted via Skype, an electronic transmission over a long distance. In the final part – an addendum, or afterthought – Baudemann contextualizes Listener as a Lakȟóta Futurism. Photos and a brief summary of the performance provide further insight into the piece. Framed as textual and visual transmissions, the short essays, transcribed dialogue, and images constitute signals in different frequencies, and they ask the reader to attune anew with every page they turn and to question again and again their own way of reading, of listening.